The Effect of Digital School Culture on Science Education and Scientific Literacy: A Scoping Review - Litina, Sanita; Rubene, Zanda (Journal of Education Culture and Society, 2024)
Thesis. In today's education scene, the incorporation of digital technology in schools has brought about a significant change beyond conventional limits, promoting a new cultural mindset known as the digital school culture. The development of “digital school culture” is one of the most prominent examples of the fusion of digital culture and school culture. The convergence of digital culture and scientific competence is becoming more evident, encompassing not only the comprehension of scientific knowledge but also the ability to adapt to swiftly evolving technologies, employ creative thinking, solve problems, make informed decisions, and apply scientific reasoning to real-world scenarios. This scoping review aims to understand the impact of digital school culture on students' scientific literacy and science educational outcomes.Concept. Digital school culture is the integration of digital technologies and educational practices in schools, involving the attitudes, behaviour, and practices of educators, students, and administrators. The key elements of digital school culture include strategy and leadership, educator preparedness, school preparedness, technological responsiveness, and digital pedagogy.Results and conclusion. This scoping review critically examines 10 studies published between 2009 and 2022, with a primary focus on components of digital school culture in science education. The review reveals that digital learning systems, digital environments to support student learning, digital technologies and tools, a digital curriculum, and pedagogical practices involving digital technology significantly improve scientific literacy.